Perineal Neurophysiological Assessment in 23 Patients Suffering from Persistent Genital Arousal Disorders: Evidence of Pudendal Neuropathy?. Issue 1 (2nd January 2016) - Villot, Anne; Thubert, Thibaul; Deffieux, Xavier; Jousse, Marylène; Breton, Frédérique Le; Lacroix, Pascal; Amarenco, Gérard
ABSTRACT: Objectives: Persistent genital arousal disorder (PGAD) is a rare condition. Our aim was to study whether or not the pudendal nerve is involved in PGAD, by means of electromyographic (EMG) testing. Methods: Twenty-three women who fulfilled the five criteria of PGAD were included in this study. After an in-depth interview and routine investigations, a perineal EMG assessment was performed. Concentric needle electromyography (EMG) testing with motor unit potential analysis of the pelvic floor muscles (bulbocavernosus muscle and striated external anal sphincter), study of the sacral reflex latency (SRL), and measurement of pudendal nerve terminal motor latency (PNTML) were performed. Results: Perineal ENMG demonstrated neurogenic changes in 14 (60.8%) of the patients. Denervation was found in all 14 patients with abnormal electrophysiological findings. Among them, 12 (85.7%) had altered PTNML and/or SRL. PTNML was delayed on the anal branch in 9 out of 14 (bilateral in 5 cases) and on the perineal branch in 9 out of 14 (bilateral in 6 cases). Conclusions : This study shows that pudendal neuropathy is frequent among women suffering from PGAD. However, due to the lack of a control group, involvement of pudendal neuropathy in the pathogenesis of PGAD remains unclear.